2010
DOI: 10.1111/j.1399-3038.2009.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet during pregnancy and allergic sensitization in the offspring by 5 yrs of age: 
a prospective cohort study

Abstract: Nwaru BI, Ahonen S, Kaila M, Erkkola M, Haapala A‐M, Kronberg‐Kippilä C, Veijola R, Ilonen J, Simell O, Knip M, Virtanen SM. Maternal diet during pregnancy and allergic sensitization in the offspring by 5 yrs of age: a prospective cohort study.
Pediatr Allergy Immunol 2010: 21: 29–37.
© 2009 John Wiley & Sons A/S To examine the effect of maternal diet during pregnancy on allergic sensitization in the offspring by 5 yrs of age. The Finnish type 1 Diabetes Prediction and Prevention Nutrition Study. A population‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 34 publications
6
86
0
6
Order By: Relevance
“…Nwaru et al [70] reported more sensitization to inhalant allergens in offspring of mothers who had consumed greater fruit and vegetable intake, particularly citrus fruit during pregnancy and the first three months of lactation. This remained significant after adjustment.…”
Section: At 5 Yearsmentioning
confidence: 99%
“…Nwaru et al [70] reported more sensitization to inhalant allergens in offspring of mothers who had consumed greater fruit and vegetable intake, particularly citrus fruit during pregnancy and the first three months of lactation. This remained significant after adjustment.…”
Section: At 5 Yearsmentioning
confidence: 99%
“…Sensitization to food allergen is a precursor and a risk factor for the development of allergic diseases later in life, which is why earliest possible detection and modification of risk indicators for food allergen sensitization might prevent the development of allergic diseases [27][28][29].…”
Section: Association Of Allergic Sensitization and Vitamin Dmentioning
confidence: 99%
“…However, there are two pathophysiological mechanisms in the development of atopic dermatitis: first, immunological mechanisms that influence the Th1/Th2 adaptive immune responses; vitamin D receptor agonists have been shown to impact on Th1 and Th2 cell function, suppress allergen-specific IgE synthesis, inhibit dendritic cell maturation and induce tolerogenic dendritic cells, and finally to induce regulatory CD4+CD25+25Foxp3+T cells. Second, injury of the skin barrier function [26,29,31]. Several recent studies have shown that infants with high level of sensitization had a decreased concentration of 25(OH)D levels [27,29,37].…”
Section: Vitamin D and Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Then it is suggested that vitamin D could skew the balance between Th1 and Th2 towards a Th2 phenotype directly or indirectly via monocyte activation, which however may be much more complex in vivo (Adams and Hewison 2008). Low vitamin D levels during pregnancy are suggested to be related in the development of food allergy (Nwaru, Ahonen et al 2010). It was recently shown that active vitamin D can suppress DC maturation and inhibit T cell proliferation.…”
Section: Influence Of Vitamins During and After Pregnancymentioning
confidence: 99%